Kreativitas Guru Dalam Penggunaan Media Power Point Pada Pembelajaran Pendidikan Agama Islam Di SMPN 2 Koto Balingka Kabupaten Pasaman Barat - Nova Yulianti; Iswantir M; Salmi Wati; Hamdi Abdul Karim (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The purpose of this study was to learn how creative the PAI teachers at SMPN 2 Koto Balingka were when using the presentation software Power Point to engage their students who were less engaged in the learning process and more likely to experience frustration and boredom. And the pitfalls that teachers have to deal with while using Power Point. This study employed a descriptive quantitative methodology.Researchers play direct roles as planners, implementers, data collectors, data analysts, and report writers.Collecting information by means of observation, interviews, and written records.Information is gathered from interviews, documents, and libraries. This study's findings suggest that teachers can boost students' understanding of a subject by being creative with Power Point presentations. This can be done by providing clear explanations of the topic at hand, coming up with unique wording for slides, and showing relevant images. Teachers can become more innovative in their use of today's sophisticated technology by making use of Power Point presentations. Students can understand the material presented. The lack of an LCD projector, the disparity between student and teacher proficiency with the PowerPoint software, and the short amount of time available for its use are all factors that dampen teachers' inventiveness while using the program.